A influência das redes estratégicas na reciclagem de material eletrônico no exterior gerando vantagem competitiva sustentável - Locher, Rony Salgado (2017)
This research investigates how strategic networks contribute to the financial and operational performance of an recycling company in the international field. The theoretical and conceptual framework includes: industrial ecology, strategic networks and sustainable competitive advantage. In the empirical part of the qualitative nature, which has the natural environment as a direct source of data and the researcher as a fundamental instrument, a case study was carried out, which is a specific process chosen for the development of this research, through exploratory research with a company Brazilian company for the recycling of electronic circuit boards, which has been operating in the market for more than 15 years, exporting this type of material for processing in secondary smelters abroad. In all, seven in-depth interviews were conducted with the managing partners of the company, and one executive of the smelter processing company abroad. From these interviews, three of them requested confidentiality of both their identities and the content presented. The rest are in this in the research described in their entirety. As results, the main findings indicate that a company to participate in a network, must have proprietary resources, its full domain and knowledge, such as: access to information, resources, markets and technologies with the advantages of learning and economies of scale And scope allowing companies to achieve their strategic objectives as risk reduction and outsourcing of the stages of the value chain and organizational functions. These resources must also be those of the other companies in the network; There must still be a durable and reliable relationship over time, a relationship that is not opportunistic and that generates mutual trust. With these elements we will have the creation of ties, which can be identified as links of common interest, which will keep the network cohesive and competitive in their respective markets. This relationship can generate over time a sustainable competitive advantage, which can express superiority of the network in relation to its competition, adding value, which can not be simultaneously implemented by other companies.